Classic highlights in porphyrin and porphyrinoid total synthesis and biosynthesis. (24th February 2021) - Senge, Mathias O.; Sergeeva, Natalia N.; Hale, Karl J.
Abstract : The development of porphyrin synthesis is illustrated, using classic and modern-day examples, which attempt to provide insights, including mechanistic ones, into the most used methods for porphyrin ring-construction and selective functionalization. Abstract : Porphyrins feature prominently in nature, be it as enzymatic cofactors, electron and exciton shuffles, as photoactive dyes, or as signaling substances. Their involvement in the generation, storage and use of oxygen is pivotal to life, while their photochemical properties are central to the biochemical functioning of plants. When complexed to metals, porphyrins can engage in a multitude of contemporary applications ranging from solar energy generation to serving as catalysts for important chemical reactions. They are also able to function as useful theranostic agents, and as novel materials for a wide range of applications. As such, they are widely considered to be highly valuable molecules, and it almost goes without saying that synthetic organic chemistry has dramatically underpinned all the key advances made, by providing reliable access to them. In fact, strategies for the synthesis of functionalized porphyrins have now reached a state of refinement where pretty well any desired porphyrin can successfully be synthesized with the approaches that are available, including a cornucopia of related macrocycle-modified porphyrinoids. In this review, we are going to illustrate the development of this exciting field by discussing a number of classic syntheses of porphyrins. Our coverage will encompass the natural protoporphyrins and chlorophylls, while also covering general strategies for the synthesis of unsymmetrical porphyrins and chlorins. Various industrial syntheses of porphyrins will also be discussed, as will other routes of great practical importance, and avenues to key porphyrinoids with modified macrocycles. A range of selected examples of contemporary functionalization reactions will be highlighted. The various key syntheses will be described and analyzed from a traditional mechanistic organic chemistry perspective to help student readers, and those who are new to this area. The aim will be to allow readers to mechanistically appreciate and understand how many of these fascinating ring-systems are built and further functionalized.